2022
DOI: 10.1007/s12264-022-00980-0
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Primary Familial Brain Calcification: Implications for Treatment

Abstract: Primary familial brain calcification (PFBC) is an inherited neurodegenerative disorder mainly characterized by progressive calcium deposition bilaterally in the brain, accompanied by various symptoms, such as dystonia, ataxia, parkinsonism, dementia, depression, headaches, and epilepsy. Currently, the etiology of PFBC is largely unknown, and no specific prevention or treatment is available. During the past 10 years, six causative genes (SLC20A2, PDGFRB, PDGFB, XPR1, MYORG, and JAM2) have been identified in PFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 166 publications
0
19
0
Order By: Relevance
“…Nimodipine, a calcium channel blocker in the CNS, has been unsuccessfully tried to attenuate PFBC symptoms [ 52 ]. Bisphosphonates, commonly used for the treatment of osteoporosis, have been reported to improve symptoms in single cases, without a demonstrated reduction in calcium deposition on CT scans [ 53 ]. In a series of seven patients, Oliveira et al observed stabilization of disease progression after administering alendronate without significant side effects, but no changes on brain calcium deposition were observed and no control group was used for comparison [ 54 ].…”
Section: Clinical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Nimodipine, a calcium channel blocker in the CNS, has been unsuccessfully tried to attenuate PFBC symptoms [ 52 ]. Bisphosphonates, commonly used for the treatment of osteoporosis, have been reported to improve symptoms in single cases, without a demonstrated reduction in calcium deposition on CT scans [ 53 ]. In a series of seven patients, Oliveira et al observed stabilization of disease progression after administering alendronate without significant side effects, but no changes on brain calcium deposition were observed and no control group was used for comparison [ 54 ].…”
Section: Clinical Managementmentioning
confidence: 99%
“…At present, treatment of PFBC-related symptoms remains symptomatic. Antipsychotics and antidepressants are used for neuropsychiatric disturbances [ 53 ]. In patients with parkinsonism, L-Dopa has been used with variable response.…”
Section: Clinical Managementmentioning
confidence: 99%
“…The insertion c.348_c.349insCTGGCCTTCCGC variant is a known pathogenic mutation ( 8 ). However, the loss-of-function c.580G > T MYORG gene variant has not been reported in ClinVar, and no publication has reported this mutation so far ( 1 3 , 8 , 11 ). Both variants were predicted to be damaging by multiple in silico prediction tools, including SIFT, Polyphen2, CADD, and MutationTaster.…”
Section: Case Presentationmentioning
confidence: 99%
“…SLC53A1 (xenotropic and polytropic retrovirus receptor 1, XPR1) is thought to be a Pi exporter and is ubiquitously expressed. Several studies have reported a correlation between altered XPR1 expression/function and placental calcification, familial brain calcification, and Fanconi syndrome [16][17][18][19][20][21]. However, how XPR1 is also involved in regulating Pi metabolism in cells and the body is unclear.…”
Section: Phosphate Transporter Classification In the Bodymentioning
confidence: 99%